THE FUTURE OF ION SENSING: INNOVATIONS IN MINIATURIZED SOLID-STATE ELECTRODES - Xiao , Feng Huang; Lei , Jun Zhao (International Journal of Civil Engineering and Architecture and Real Estate, 2024)
The electrochemical method, a technique reliant on the distinctions in properties among diverse substances, hinges on the detection of electrical signals within the testing detection system [1]. In contrast to conventional methods such as titration, spectroscopy, and chromatography that analyze the total concentration of ions, the ion-selective electrode (ISE) operates on a distinct principle. It converts the ion activity to be measured into an electromotive force. Functioning as potent potentiometric chemical sensors, ion-selective electrodes (ISEs) offer a range of merits, including compact dimensions, rapid response times, user-friendliness, and costeffectiveness. They have found extensive application in environmental monitoring, industrial analysis, and clinical testing [2]. Notably, the ion-selective electrode method's detection limit remains unaffected by the sample quantity, rendering it particularly suitable for microanalysis. The innovation of the all-solid-state ionselective electrode is a noteworthy evolution in this domain. It substitutes the conventional filling liquid in liquid-junction ionselective electrodes with a solid-state conversion layer. This ingenious substitution circumvents the shortcomings associated with traditional liquid-junction ion-selective electrodes, such as filling liquid leakage and limited miniaturization capabilities. Contrasting with its liquid-junction counterparts that often possess a relatively large volume, the all-solid-state ion-selective electrode showcases inherent ease of integration and miniaturization. Researchers have recognized the potential of a new all-solid-state ion-selective electrode devoid of inner liquid, paving the way for innovative developments in this field